1973
DOI: 10.1021/ja00782a034
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of selenium with sodium borohydride in protic solvents. A Facile Method for the introduction of selenium into organic molecules

Abstract: Elemental powdered selenium and sodium borohydride react very readily in water or ethanol to give either sodium hydrogen selenide or sodium diselenide, depending on the ratio of the reactants. The sodium hydrogen selenide and sodium diselenide solutions, thus prepared, can be utilized directly in typical nucleophilic displacement reactions. Alkali metal borohydrides have been combined l with the chalcogen elements by direct fusion1•2 and in aprotic solvents such as ether,2 dioxane,8 tetrahydrofuran,4•5 and dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
260
0
5

Year Published

1980
1980
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(267 citation statements)
references
References 2 publications
(4 reference statements)
2
260
0
5
Order By: Relevance
“…There is no excessive NaBH4 left and no metal ions are reduced (except the reduction of Cu 2+ into Cu + ). [42][43][44] Hence different from the literatures, [39,41] there is no metal nanoparticles formed and no disproportion of Se/Te happened during the whole preparation.…”
Section: Resultsmentioning
confidence: 72%
“…There is no excessive NaBH4 left and no metal ions are reduced (except the reduction of Cu 2+ into Cu + ). [42][43][44] Hence different from the literatures, [39,41] there is no metal nanoparticles formed and no disproportion of Se/Te happened during the whole preparation.…”
Section: Resultsmentioning
confidence: 72%
“…We have now found that substituted tellurobenzoic acid-Te-benzjd-esters (1) can be obtained by a phase transfer technique when certain benzoyl chlorides in toluene are treated with sodium telluride generated in water solution [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…The Mutation of Ser Residues in scFv2F3-Sodium hydroselenide was prepared according to the method described (22). The mutation of Ser residues in scFv2F3 was performed according to Ref.…”
Section: Methodsmentioning
confidence: 99%